Aberrant amygdala intrinsic functional connectivity distinguishes youths with bipolar disorder from those with severe mood dysregulation. Issue 2 (28th February 2015) - Stoddard, Joel; Hsu, Derek; Reynolds, Richard C.; Brotman, Melissa A.; Ernst, Monique; Pine, Daniel S.; Leibenluft, Ellen; Dickstein, Daniel P.
Abstract: It remains unclear the degree to which youths with episodic mania (bipolar disorder; BD) vs. those with chronic, severe irritability (severe mood dysregulation, SMD) should be placed in similar or distinct diagnostic groups. Addressing this clinically meaningful question requires greater understanding of the neural alterations underlying both disorders. We evaluated resting state functional magnetic resonance imaging data of 53 youths (14 BD, 20 healthy volunteers (HV), and 19 SMD, ages 9–18.5 years). Seed regions of interest were the bilateral basolateral, superficial and centromedial amygdala, defined using the Juelich probabilistic atlas. We found a significant between-group difference in functional connectivity between the left basolateral amygdala and the medial aspect of the left frontal pole plus the posterior cingulate/precuneus. This finding was driven by hyperconnectivity among BD vs. HV or SMD youths. As with earlier data, these findings suggest that the pathophysiology of BD and SMD may differ. Highlights: Youths with a history of episodic hypomania or mania (BD) differ from youths with severe, chronic irritability (SMD) in intrinsic functional connectivity (iFC) between the left basolateral amygdala and the medial prefrontal cortex, posterior cingulate, and precuneus—suggesting that they are distinct clinical phenotypes. Relative to healthy volunteers, those with BD show increased iFC between the amygdala and these regions, suggesting that hyperconnectivity between the amygdala and prefrontal cortex, precuneus, and posterior cingulate is a feature of BD.